Non coverage of Hepatitis B immunization among children and its predictors in northeastern states of India: A multiscale geographically weighted regression analysis - Shefali Gupta; Kh. Jitenkumar Singh; Krishna Kumar; Md Asif Khan; Roopmala Gupta; Saurabh Sharma (Journal of Family Medicine and Primary Care)
Background: Hepatitis B, a viral infection, is a vaccine-preventable disease and is a significant public health challenge globally. Child immunization is a safe and effective way to prevent Hepatitis B virus infection. The Universal Immunization Programme (UIP) of India, which effectively reduces the chronic burden, aims to reach immunization of nearly 2.67 crore newborns annually. Under this program, the Hepatitis B vaccine was introduced in 2007–2008. This study aims to assess the level and trend and identify spatial hotspots of noncoverage of Hepatitis B immunization and its predictors in northeastern states of India. Methods: This study used cross-sectional survey data from the National Family Health Survey-5 (2019–21) of 6380 children aged 12–23 months in northeastern states. We used Moran’s I and Getis-Ord Gi* statistics to investigate spatial autocorrelation and hotspots of noncoverage of Hepatitis B immunization. Additionally, we applied Multiscale Geographically Weighted Regression (MGWR) to assess its predictors for noncoverage of Hepatitis B immunization. Results: Spatial hotspot analysis results showed that noncoverage of Hepatitis B immunization was found in most of the districts in Nagaland, Manipur, Eastern and Central regions in Meghalaya, Cachar valley districts and the lower part in Assam, and a few districts in Arunachal Pradesh. Besides, MGWR results indicated that the proportion of the poorest wealth index, children of higher birth order, mothers with no media exposure, and those seeking care from private healthcare facilities were significant predictors for noncoverage of Hepatitis B immunization. Conclusion: Noncoverage of Hepatitis B immunization highlighted the clustered levels in northeastern states of India. This study provides valuable insights for policymakers and stakeholders in designing community-specific interventions, formulating policies, and conducting epidemiological research.